Design and fabrication of grating couplers for the optical addressing of trapped ions - Lim, Yu Dian (2021)
In this work, silicon photonics structures for the optical addressing of trapped ion is developed for quantum computing applications. Grating-waveguide-grating structures of various designs are designed, and fabricated for various radius curvatures of 12, 15, 25 and 30 μm, respectively. From the optical measurements, gratings with radius of curvature of 25 and 30 μm exhibit lower power loss of 36.5 and 33.9 dB with better-focused beam profiles as compared to those with radius of curvature of 12 and 15 μm. The beam width from these gratings ranges between 17.31 to 41.54 μm, which provides the feasibility to perform optical addressing on 2 to 4 Sr+ ions trapped along the ground electrode of the ion trap.